Molecular Characteristics and Distribution of Virulence Genes among Staphylococcus aureus Complex Isolates Derived from Vascular Access Infections. (21st October 2022) - Wong, Min Yi; Tseng, Yuan-Hsi; Huang, Tsung-Yu; Chu, Chishih; Lin, Bor-Shyh; Huang, Yao-Kuang
Abstract : Staphylococcus aureus is a major human pathogen that produces various virulence factors which promote the binding of bacteria to tissues and medical devices such as vascular access devices, thereby developing a wide range of invasive infections. Vascular access serves as an entry site for S. aureus and elevates the risk of infection in the hemodialysis population. Nevertheless, the distribution of virulence genes in Staphylococcus spp. associated with vascular access infections (VAIs) has not been studied previously. In this study, we determined the relationship between the molecular characteristics and virulence profiles of S. aureus isolates obtained from VAIs. We collected isolates from patients with VAIs between August 2017 and December 2020 and further analyzed the molecular characteristics, antimicrobial resistance profiles, and virulence gene distribution in the isolates. Overall, 15 sequence types (STs), including a new ST (ST6892) and 19 spa types, were identified among the 56 isolates. Of the 53 S. aureus isolates, ST8, ST239, ST45, and ST59 were the predominant STs, whereas ST2250 was the only ST in 3 S. argenteus isolates. ST45-SCC mec IV-t026 (abbreviated as ST45-IV-t026), ST59-V-t437, and ST8-IV-t008 were the predominant clones that belonged to agr type I. All isolates harbored clfB and eno, whereas all S. aureus isolates harbored clfA . In addition, 10 Panton-Valentine leucocidin-positive isolates belonged to ST8 and ST59, with ST8-IV-t008 and ST59-V-t437 being the predominant clones. In brief, the distribution of virulence genes associated with STs may assist in the spread of molecular types of Staphylococcus spp.